The Relationship between Emotional Intelligence and Innovative Work Behavior - Abdullah, Nor Hazana; Lai, Yun Xuan; Abdul Hamid, Nor Aziati; Takala, Josu; Wahab, Eta (Journal of Techno-Social, 2021)
Researchers agree that innovation is one of the competitive business strategies to ensure sustainability of local small and medium sized enterprises (SMEs) in the global market. However, the level of innovative work behavior (IWB) among Malaysia’s SMEs is not encouraging. Studies have claimed that emotional intelligence as one of the precursors of innovative work behavior. Emotional intelligence (EQ) enables employees to disseminate and implement innovative ideas more effectively as they have the abilities to understand and manage their own emotion and others. Thus, this study aimed to examine the relationship between emotional intelligence and its respective dimensions with innovative work behavior among employees working in food and beverage (F&B) medium sized enterprises. The research is quantitative research questionnaires as data collection method. A total of 400 questionnaires were collected from F&B medium sized enterprises’ employees located at Selangor, Kuala Lumpur, Johor, Perak, and Penang via quota sampling. Descriptive analysis confirmed that the level of IWB is moderate in line with previous studies. EQ explained 25.7% variance in IWB with self-management has the strongest influence. This finding implies that selection and hiring of employees should consider the use of EQ for testing.